Colour vision deficiency among medical students of Chitwan - Bhusal, Pujan; Timilsina, Sameer; Yadav, Ram Lochan; Sapkota, Niraj Khatri; Islam, Md Nazrul (Journal of Chitwan Medical College, 2020)
Background: Colour vision is the function of three types of cone pigments present in the retina. Though colours are used for important signs in the medical profession, screening for colour blindness is not paid attention at beginning of a medical career. This study was aimed to assess the presence of colour blindness, if any among the medical students of Chitwan Medical College. Methods: A total of 220 medical students including 127 females and 93 males aged between 16-24 years were examined for colour blindness. Students were shown the complete range of Ishihara’s plates under daylight conditions. The chart was held 75 cm away from the subjects. The types of colour vision deficiency were differentiated with help of key provided with the chart. The data was analyzed by using Statistical Package for the Social Sciences version 20. Results: Among 220 participants, 5(2.27%) were found to have colour vision deficiency. Out of 5colourdeficient students, 4of them were red-green colour vision deficient and 1 of them couldn’t appreciate colour (total colour blindness) within the speculated time for the test. Female participants didn’t have colour vision deficiency while colour vision deficient students were unaware of their colour vision status. Conclusions: Colour vision deficiency affects male than female. Medical students should be screened for colour vision deficiency and made aware of their limitation so that they can take special care in their future clinical practice.